A critical survey of integrated energy system: Summaries, methodologies and analysis. (15th August 2022) - Song, Dongran; Meng, Weiqi; Dong, Mi; Yang, Jian; Wang, Junlei; Chen, Xiaojiao; Huang, Liansheng
Highlights: Visual analysis of 1998 articles on Integrated Energy System through CiteSpace. Comprehensive classification of model methods with sub-classifications. Various operation optimization methodologies are summarized thoroughly. Twenty-two model tools are classified and analyzed comprehensively. Several insightful challenges and perspectives are discussed. Abstract: With a rapid growth of Integrated Energy System (IES) in various scenarios, researches on IES have attracted extensive attention in the last few decades. Inspired by the ever-increasing studies about the IES, which focus on various energy scenarios but lack a systematic summarization, this paper aims to undertake a comprehensive review of the IES models, operation optimization methods, and model tools. Firstly, CiteSpace is used to visually analyze the cooperation and co-occurrence network of related articles in recent two decades, among which 1998 papers from WOS are selected for analyzing. Note that 243 papers highly related to IES are further investigated to systematically analyze and integrate the relevant work. On this basis, different definitions of IES around the world and 12 related research hotspots are summarized. Then, the IES modeling methods are creatively classified from eight aspects. Furthermore, from the perspective of operation optimization methods, three mainly optimal problems, including Economic Dispatch, Unit Commitment and Optimal Power Flow, are comprehensively analyzed. Besides, 22 energy model tools are discussed from the levels of National, Regional, and Users. Finally, seven advantages and three challenges are summarized, four key points are concluded, and six perspectives/recommendations are proposed for future research. In general, this paper is intended to offer an insightful guidance to prompt related researchers/engineers to broaden the horizons of their researches.